2020
DOI: 10.1111/aec.12911
|View full text |Cite
|
Sign up to set email alerts
|

LupinuspolyphyllusLindl. andRumex acetosellaL. effects on nutrient accumulation and microbial activity on tephra from the Puyehue–Cordón Caulle eruption (2011)

Abstract: This study investigated the capacity of Lupinus polyphyllus (Leguminosae) and Rumex acetosella (Polygonaceae) to promote nutrient accumulation and microbial activity on tephra from the volcanic eruption of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The mean annual rainfall is 2000 mm and temperature ranges from a summer mean of 13.5 C to a winter mean of 2.9 C (Weather Station Villa La Angostura 2016). The soils buried by the volcanic tephra were Andisols (USDA Soil Taxonomy), and had been previously studied by Satti et al (2007) who reported the following physicochemical characteristics: 6.3 of pH, 0.08 dS/m electrical conductivity, 7.3 mg/kg extractable Olsen-P, 0.48% total N and 10.8% organic C. Regarding the 30 cm of tephra that buried these soils in 2011, they presented the following characteristics: 6.5 of pH, 0.02 dS/m electrical conductivity, 0.7 mg/kg extractable Olsen-P, 0.003% total N and 0.02% organic C. In 2013, this tephra layer had already compacted to 13 cm in the roadsides and 15 cm in the forest (Ferreiro et al 2020c).…”
Section: Study Areamentioning
confidence: 98%
See 1 more Smart Citation
“…The mean annual rainfall is 2000 mm and temperature ranges from a summer mean of 13.5 C to a winter mean of 2.9 C (Weather Station Villa La Angostura 2016). The soils buried by the volcanic tephra were Andisols (USDA Soil Taxonomy), and had been previously studied by Satti et al (2007) who reported the following physicochemical characteristics: 6.3 of pH, 0.08 dS/m electrical conductivity, 7.3 mg/kg extractable Olsen-P, 0.48% total N and 10.8% organic C. Regarding the 30 cm of tephra that buried these soils in 2011, they presented the following characteristics: 6.5 of pH, 0.02 dS/m electrical conductivity, 0.7 mg/kg extractable Olsen-P, 0.003% total N and 0.02% organic C. In 2013, this tephra layer had already compacted to 13 cm in the roadsides and 15 cm in the forest (Ferreiro et al 2020c).…”
Section: Study Areamentioning
confidence: 98%
“…Microbial communities release hundreds of enzymes into the environment by secretion and cell lysis, however, the ones of interest in plant litter decomposition rate are those directly involved in the degradation of lignocellulose and the cycling of nitrogen, phosphorus, and sulfur (Sinsabaugh et al 1991). Enzymes mineralyzing N (leucine‐aminopeptidase) and P (acid phosphomonoesterase), and degrading lignin (phenol oxidase) and cellulose (β‐glucosidase) have previously provided information on substrate microbial and plant rhizosphere activity in “De los Siete Lagos” tephra (Ferreiro et al 2018, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…There they have affected the native flora of the subantarctic Prince Edward Island which is of relatively recent volcanic origin. R. acetosella, which is native to Europe and southwestern Asia, has spread throughout many regions of the globe and is considered very invasive in several areas (Stopps et al 2011, Ferreiro et al 2020 Invasive Species Database 2022c). L. arenarius, native to Europe, has been introduced at sites by the Great Lakes in North America.…”
Section: Characteristics Of Individual Speciesmentioning
confidence: 99%